2020
DOI: 10.1002/dac.4397
|View full text |Cite
|
Sign up to set email alerts
|

A novel heuristic simulation‐optimization method for critical infrastructure in smart transportation systems

Abstract: Summary A simulation‐based optimization is a decision‐making tool that helps in identifying an optimal solution or a design for a system. An optimal solution and design are more meaningful if they enhance a smart system with sensing, computing, and monitoring capabilities with improved efficiency. In situations where testing the physical prototype is difficult, a computer‐based simulation and its optimization processes are helpful in providing low‐cost, speedy and lesser time‐ and resource‐consuming solutions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Intuitionistic fuzzy set theory deals with both membership and nonmembership values. Neutrosophic set theory developed by Smarandache treats uncertainty and ambiguity by adding indeterminacy-membership functions, in addition to truth-membership and falsity-membership functions [18][19][20][21][22].…”
Section: Schedule Algorithms • Event Oriented Networkmentioning
confidence: 99%
“…Intuitionistic fuzzy set theory deals with both membership and nonmembership values. Neutrosophic set theory developed by Smarandache treats uncertainty and ambiguity by adding indeterminacy-membership functions, in addition to truth-membership and falsity-membership functions [18][19][20][21][22].…”
Section: Schedule Algorithms • Event Oriented Networkmentioning
confidence: 99%
“…Challenges identified in blockchain-based smart healthcare literature surveys are: (i) lack of proper knowledge in healthcare system users to effetively and securly storage of data, and access as and when required, (ii) lack of standard data collection templates, sharing platforms, peer-to-peer connectivity systems, trust in existing healthcare system etc. (iii) proper dynamic framework that ensures secure data migrations from present healthcare system to smart healthcare system, (iv) many developing countries lacks in intentions to provide corruption free or unethical economic benefit based health services, (v) management of EHR, EMR or PHR, (vi) custodian based secure data accessibility, (vii) connectivity among medical technologists to help in developing full-proof system, (viii) many countries do not have standarization policies for cryptocurrencies, (ix) secure management of data in densly populated regions or countries, (x) users are not interested to invest in companies which can handle their historical or ancestral records on payment basis even by knowing that they themselve are not able manage their records which are very much necessary in any treatment, (xi) lack in technological solutions like (usage of industry 4.0 or simulationoptimization) in healthcare for making it advanced and secure [39]- [41], (xii) a large number of data leakage and unethical advantages are observed in present healthcare system, and (xiii) unmanaged present healthcare system with failures, thefts, eavesdropping, spoofing, impersonation or other cybercrimes.…”
Section: Literature Surveymentioning
confidence: 99%
“…Kumar et al suggested a heuristic algorithm for providing QoS in smart transportation system [21]. Although the proposed method enhances the network performance, it cannot be applied for a larger smart network.…”
Section: Environmental Informationmentioning
confidence: 99%